PENGARUH BEBAN KERJA TERHADAP STRESS KERJA MELALUI DUKUNGAN SOSIAL SEBAGAI VARIABEL INTERVENING - minda tri wulandari (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
ABSTRACT The purpose of this study is to describe (1) the influence of workload on work stress, (2) the influence of workload variable on social support, (3) influence of work stress variable to social support, (4) influence of workload variable to work stress through social support as intervening variable at Depok Barat Police Departement. This research belongs to the type of quantitative research. The population is all members of the police “Polsek Depok Barat” of the rank of Bintara with a total 63 peoples who are also used as sample research. Methods of data collection using questionnaires, while data analysis techniques using linear regression, path analysis and Sobel test with SPSS 18.00 for windows. The result of data analysis with significance 0,05 indicate that work load has a significant positive effect to work stress; workload has a positive and significant effect to social support; work stress have a significant positive effect to social support; and work load have a positive and significant effect on work stress through social support as variael intervening.